2021
DOI: 10.1002/soej.12541
|View full text |Cite
|
Sign up to set email alerts
|

International trade, differentiated goods, and strategic asymmetry

Abstract: We scrutinize international trade arising from oligopolistic rivalry (reciprocal dumping) in a model where the goods are horizontally differentiated and where otherwise symmetric firms located in different regions adopt asymmetric strategies-one competing in prices and the other competing in quantities. Unidirectional and intra-industry trade appear endogenously in our framework. We show that as trade costs decline the equilibrium outcome will transition from autarky through a region of unidirectional trade, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Such asymmetric strategies have been observed also among exporters of mass-produced versus custom-made goods (Schroeder & Tremblay, 2015;Schroeder & Tremblay, 2016), as well as in the market for small cars and in the aerospace connector industry in the United States (Tremblay & Tremblay, 2011), and in the Japanese home electronics industry (Sato, 1996). See, Gilbert et al (2022) for further details on the anecdotal and indirect evidence reported by the literature. 3 See Grassman (1973) for evidence on invoicing practices of exporters in the context of bilateral trade between Sweden and the U.S.; Magee (1974) on the currency of denomination of contracts of Japanese and German exporting firms to the U.S.; Page (1977) and Carse et al (1980) on invoicing practices of British exporters; and Van Nieuwkerk (1979) on invoicing practices of Dutch exports and imports.…”
Section: Data Availability Statementmentioning
confidence: 91%
See 3 more Smart Citations
“…Such asymmetric strategies have been observed also among exporters of mass-produced versus custom-made goods (Schroeder & Tremblay, 2015;Schroeder & Tremblay, 2016), as well as in the market for small cars and in the aerospace connector industry in the United States (Tremblay & Tremblay, 2011), and in the Japanese home electronics industry (Sato, 1996). See, Gilbert et al (2022) for further details on the anecdotal and indirect evidence reported by the literature. 3 See Grassman (1973) for evidence on invoicing practices of exporters in the context of bilateral trade between Sweden and the U.S.; Magee (1974) on the currency of denomination of contracts of Japanese and German exporting firms to the U.S.; Page (1977) and Carse et al (1980) on invoicing practices of British exporters; and Van Nieuwkerk (1979) on invoicing practices of Dutch exports and imports.…”
Section: Data Availability Statementmentioning
confidence: 91%
“…Foreign market entry modes and the corresponding welfare implications are, however, not considered. Gilbert et al (2022) have demonstrated that analyzing asymmetric choices in strategic variables in the context of international trade is important.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Foster (2008), countries can benefit from liberalisation most in the long run, but they can suffer from short-run adverse effects of liberalisation. The effects of product differentiation and changing trade costs for trade intensity are asymmetric (Gilbert et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%